2019
DOI: 10.1080/20009666.2019.1618135
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of 30-day readmission in spontaneous pneumothorax in the United States: a nationwide retrospective study

Abstract: Objective : Our study aimed to determine the national estimates of the 30-day all-cause readmission rate among patients with spontaneous pneumothorax and to investigate the burden of these readmissions in terms of mortality, length of stay and hospitalization costs in the USA. Methods : We utilized the Nationwide Readmission Database for 2013–2014 and identified adults with a primary diagnosis of spontaneous pneumothorax. We analyzed and reported patient- and hospital-level v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…14 It is noteworthy that the incidence of 30-day unplanned readmission in PSP patients is reported to be 13.6%, and middle age and history of cancer are two independent risk factors for readmission. 18 Mechanical pleurodesis is widely used with the aim to decrease the risk of postoperative recurrence of PSP after bullectomy, while there is little evidence of this to date. A trial showed that the application of mechanical pleurodesis did not significantly decrease the incidence of PSP recurrence compared with simple wedge resection.…”
Section: Discussionmentioning
confidence: 99%
“…14 It is noteworthy that the incidence of 30-day unplanned readmission in PSP patients is reported to be 13.6%, and middle age and history of cancer are two independent risk factors for readmission. 18 Mechanical pleurodesis is widely used with the aim to decrease the risk of postoperative recurrence of PSP after bullectomy, while there is little evidence of this to date. A trial showed that the application of mechanical pleurodesis did not significantly decrease the incidence of PSP recurrence compared with simple wedge resection.…”
Section: Discussionmentioning
confidence: 99%
“…Complication rates were significantly higher for TTNA than for RB (17% vs. 4.4%) [ 47 ]. The average cost for an admission for primary spontaneous pneumothorax has been retrospectively estimated at $13,961 ± $15,789, with total costs of $52,118 ± $69,490 [ 48 ], and this does not include the cost of the staging bronchoscopy that is required for positive lesions. Future prospective studies will likely be able to demonstrate cost benefit over, or at least cost parity with, TTNA at the system level.…”
Section: Advantages Of Robotic Bronchoscopymentioning
confidence: 99%